164k views
1 vote
Neveah has created the function of f(x) = 2x+4/3 to represent the growth of her hair, where x represents the number of months since her last haircut. Neveah discovers that, using inverse function to solve for X=6, she can predict when her hair will have grown 6". Explain to Neveah how to accomplish this using complete sentences.

2 Answers

2 votes

Answer:

Expert Verified Answer? LOL!! Who is this expert?

Explanation:

If the "Expert Verified Answer" above was correct, we could then substitute 2.33 into the original equation and it would equal 6

Let's try:


(2(2.33)+4)/(3)


\frac{4.66+4}3}


(8.66)/(3) = 2.88666667 Yeah, sure. That would round up to 6, right?

Professor1991 screwed it up and some "expert" said, "Looks good enough for me!"

Do your own work people, and stop using "Experts" to do your work for you! You're going to fail!

User Benny Davidovitz
by
5.2k points
3 votes
f(x)=2x+4/3

Replace f(x) by y:
y=2x+4/3

Solving for x:
y-4/3=2x+4/3-4/3

Subtracting the two terms on the left side of the equation:
(3y-4)/3=2x

Dividing both sides of the equation by 2:
[(3y-4)/3]/2=2x/2
[(3y-4)/3]*(1/2)=x
[(3y-4)*1]/[(3)*(2)]=x
(3y-4)/6=x
x=(3y-4)/6

Replace "x" by "f^(-1) (x)" (inverse function) and "y" by "x":
f^(-1) (x) = (3x-4)/6 Inverse function

Then, for x=6
f^(-1) (6) = [ 3(6)-4]/6
f^(-1) (6) = (18-4)/6
f^(-1) (6)= 14/6
f^(-1) (6) = 7/3

Her hair will have grown 6 after 7/3 = 2.33 months


User Gaby Fitcal
by
5.4k points